2010
DOI: 10.1080/01635581.2010.492085
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High Dose, Aglycone-Rich Soy Extract on Prostate-Specific Antigen and Serum Isoflavone Concentrations in Men With Localized Prostate Cancer

Abstract: The efficacy and safety of consuming high-dose isoflavone supplements for prostate cancer is not clear. A double-blind, placebo controlled, randomized trial was conducted in 53 men with prostate cancer enrolled in an active surveillance program. The treatment group consumed a supplement containing 450 mg genistein, 300 mg daidzein, and other isoflavones daily for 6 mo. Prostatespecific antigen (PSA) was measured in both groups at baseline, 3 mo, and 6 mo, and serum concentrations of genistein, daidzein, and eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 41 publications
1
71
1
1
Order By: Relevance
“…Two randomized, double-blind, placebo-controlled short-term isoflavone intervention trials before radical prostatectomy have shown that genistein failed to change the PSA levels significantly, even though it modulated the expression of several genes involved in prostate cancer (43,44). A 6-month double-blind, placebo-controlled intervention study with highdose soy extracts conducted in 53 men with prostate cancer enrolled in an active surveillance program also failed to show lower PSA levels (45). Conversely, soy extracts appear to be more efficient when combined with other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized, double-blind, placebo-controlled short-term isoflavone intervention trials before radical prostatectomy have shown that genistein failed to change the PSA levels significantly, even though it modulated the expression of several genes involved in prostate cancer (43,44). A 6-month double-blind, placebo-controlled intervention study with highdose soy extracts conducted in 53 men with prostate cancer enrolled in an active surveillance program also failed to show lower PSA levels (45). Conversely, soy extracts appear to be more efficient when combined with other compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, intake of an aglycone isoflavone supplement (containing 450 mg genistein, 300 mg daidzein, and other isoflavones daily for 6 months) in a group of 53 prostate cancer patients displayed high plasma levels of genistein (39.85lM) and daidzein (45.59 lM) (deVere White et al 2010). Moreover, data in humans and animals showed that concentrations of flavonoids in the endocrine-responsive tissues including liver, mammary gland, ovary, prostate, and uterus may exceed plasma levels several fold (Gardner et al 2009;Chang et al 2000;Janning et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, numerous biomarkers have been identified, including PSA, prostate-specific membrane antigen, PSCA, early prostate cancer antigen, B7-H3, chromogranin A, α-methylacyl coenzyme A racemase, glutathione S-transferase P1 (GSTP1), sarcosine, caveolin-1, TMPRSS2-ERG, Ki-67, prostate cancer antigen 3 (PCA3) and disabled homolog 2-interacting protein (35). Previous studies have demonstrated that a number of these biomarkers, including PSA, GSTP1, Ki-67 and PCA3, were the targets by which flavonoids exerted anticancer effects in prostate cancer (36)(37)(38)(39). Using human xenografts grown in mice with severe combined immunodeficiency, it has also been demonstrated that anti-PSCA monoclonal antibodies inhibited the growth and metastasis of tumors (40), thus indicating that PSCA may be an immunotherapeutic target in the treatment of prostate cancer (40,41).…”
Section: Discussionmentioning
confidence: 99%